Morphological patterns of anaemia among pregnant women from Sudan - Abuobieda B. Abusharib (AOSIS, 2019)
Background: Morphological patterns of anaemia in pregnancy are considered essential for classification, diagnosis and management of patients, especially in regions with high maternal mortality like Sudan. Objectives: This study evaluated morphological patterns of anaemia among pregnant women in Sudan and morphological differences across characteristics of participants. Methods: This cross-sectional study was conducted from September 2016 to February 2017. A total of 200 women were selected according to specific criteria. Laboratory tests were performed for complete blood count, blood smears were performed for morphology and vitamin B12, folate and iron levels were measured. Participants were classified as: normochromic normocytic, microcytic hypochromic, macrocytic or dimorphic. Further classification based on haemoglobin levels was also performed. Results: A total of 116 participants (58%) had a dimorphic pattern, followed by 50 participants (25%) with a microcytic hypochromic pattern, 20 participants (10%) with a macrocytic pattern and 14 participants (7%) with a normochromic normocytic pattern. Participants with the dimorphic pattern also had low levels of iron and folate. The majority of dimorphic participants presented with mild anaemia, whereas the majority of participants with the microcytic hypochromic pattern presented with moderate or severe anaemia. A high percentage of participants in late pregnancy had the dimorphic pattern, and there were significant differences in the degree of anaemia by parity, gestational age and regular intake of haematinic supplements. Conclusion: The most frequent morphological pattern of anaemia in this study was dimorphic, followed by microcytic hypochromic, macrocytic and normochromic patterns. Morphological patterns appeared to predict types of vitamin and mineral deficiency and the degree of anaemia.